Menumbuhkan Berpikir Kritis pada Siswa melalui Peran Guru dan Peran Sekolah - Nantara, Didit (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2021)
Education is a process that people go through with certain methods to gain knowledge, understanding, and how to behave according to their needs. One of the efforts to improve the quality of education is to increase quality human resources (HR). Improving the quality of human resources focuses on critical thinking skills. This is an important agenda and a vital issue in modern education in the era of globalization. Schools as educational institutions that provide knowledge or experience to students in accordance with the demands of the 21st century are required to be able to foster critical thinking through various activities. Through literature review it is known that critical thinking is an organized process made possible by students in evaluating evidence, assumptions, logic, and the language that underlies other people's statements. To foster critical thinking in students, the role of the teacher and the role of the school is needed. In fostering critical thinking in students through the role of the teacher, it can be done through learning activities and giving HOTS questions. Meanwhile, the role of the school can be carried out through extracurricular activities, the school literacy movement, and the student council. From these conclusions, it is suggested for teachers to develop other learning strategies and assessments that help students in higher order thinking, and for schools to develop other activities that form critical thinking patterns in students in solving problems independently and being able to filter the information that enters them.